Tips on housemanship you wish you knew before - Hambali, Zarida; Idris, Faridah; Hod, Rafidah (Penerbit Universiti Tun Hussein Onn, 2016)
Understanding what it feels like to go through the hard, challenging life as a young house officer equipped with knowledge but with zero experience, we strive to come up with the best tips and important highlights to ensure your journey through housemanship is less painful. Chapters covers all the major postings as well as providing useful insights into radiology, anaesthesiology and pathology-related matters. We have also incorporated a chapter on how to cope with housemanship. Knowing how stressful it can be - fear of the unknown, unexpected, unfamiliar working conditions in the hospital may be detrimental to those who do not posses good survival skills. This book is specially dedicated to our students who are just about to venture out into the thrilling and challenging world of housemanship.